Mario Osorio Marques: Educational action with lovingness, the paths of human rights (Revista Contexto & Educação, 2025)
This article aims to analyze, based on a study of the life and work of Mario Osorio Marques, the profile of his educational action and its relationship with the precepts of Human Rights. By examining the different phases of his life, from his different actions, from religious life, to social life, to intellectual production in the academic world, it is possible to identify something that sets him apart, attributing originality to his Being as a person and his actions, the expression of a differentiated educational action, filled with lovingness. That is, the expression of an educational action with lovingness expressed beyond institutionalized environments of teaching, but also in personal life, in moments of meetings, in social action with the perspective of seeking to improve social life, in his writings and in his diverse intellectual action.
Keywords: Mario Osorio Marques; Educational Action; Lovingness